Evidence for dynamic kagome ice - E. Lhotel (Nature Portfolio, 2018)
Quantum ferromagnetic spin liquids in two dimensions, namely quantum kagome ices, yield exotic magnetic properties but their identification remains challenging. Here the authors investigate a dynamic kagome ice state in the pyrochlore oxide Nd2Zr2O7 by magnetization and neutron scattering measurements.